The Issue Isn’t Which Model of Consumer Interference Is Right, but Which One Is Least Wrong - Ginzburg, Lev R.; Damuth, John (Frontiers in Ecology and Evolution, 2022)
Empirical observations and an analogy with the history of ballistics illuminate the ongoing debate about the default choice for types of functional responses, based on consumer interference. The two ideal views of consumer interference are: (1) There is no direct mutual interference among consumers (“prey-dependence”), and (2) Consumers show strong mutual interference, the functional response depending on the number of prey per consumer (“ratio-dependence”). Each of these minimal-information concepts are what we refer to as “root” models, of limited accuracy in themselves, but they are the base upon which we erect complex models for specific, real-world cases. We argue that the ratio dependent view coincides more naturally with the way we model the dynamics of any population, and taken alone it is the model more consistent with empirical observations. Both root models often will give the “wrong answer” when applied directly to real world cases. Nevertheless, one root model may be “less wrong” than the other. This is not unlike developments 400 years ago in physics, when two root models competed in ballistics. Galileo’s demonstration that the default trajectory of a projectile is a parabola eventually replaced what had been the dominant root model since Aristotle. Both ballistic root models are inaccurate in the presence of air friction, but the parabolic model is, overall, less wrong. We argue that the ratio-dependent model, like the parabolic trajectory, is the “less wrong” and it is therefore a natural view from which to start thinking about consumer-resource interaction and developing more elaborate models.